Immediate loading in edentulous maxilla - A case report - Bogdan Mihai Gălbinaşu; Veronica Bucur; Ion Pătraşcu (Amaltea Medical Publishing House, 2021)
The main objective of inserting dental implants in various clinical situations is to avoid mobile prosthetic restorations or to obtain a better stability. In this way, patients are offered increased comfort and better integration of prosthetic restorations into the stomatognathic complex. The purpose of this case presentation is to highlight a case of complex oral rehabilitation in which the Sky Fast and Fixed system (Bredent GmbH, Senden, Germany) was chosen, in the case of maxillary restoration, thus avoiding a mobile prosthetic restoration. The result demonstrates a superior aesthetic rehabilitation than the initial situation, obtaining a significant improvement from the first treatment session.